UPAYA MENGARAHKAN LANSIA MENJADI SDM YANG TANGGUH DI BIDANG PROFESIONAL VOKASIONAL - Syafrida Syafrida (Universitas Negeri Medan, 2014)
ABSTRACTThe elderly people are entitled to educational maintenance attention and special assistance sponsored by country. So far those who have not been classified as a potential Elderly. Need to prepare qualified human resources in order to develop the Strenght of Elderly Family Development with Seven Dimensions. One of these dimensions will be visualized in this journal of vocational Professional Dimensions. Development of guidance to the elderly via this dimension can be based on a hobby; creative economy; and entrepreneurship is ingrained in the elderly. We have to move on and should be any vocational education. Kata Kunci : Profesional Vokasional, Lansia.